The proteomic architecture of clonal hematopoiesis: a systematic review of niche remodeling and multi-compartment predictors of malignant transformation - Jana H. Husein; Rasha M. Khayata; Aisha Jahangir; Ghaith K. Mansour; Ahmed W. Hajjar; Muhammad Raihan Sajid (Frontiers in Medicine, 2026)
Background Clonal hematopoiesis of indeterminate potential (CHIP) is a precursor to myeloid malignancies, yet the functional proteomic landscape that governs clonal fitness and microenvironmental remodeling remains poorly understood. This systematic review consolidates high-resolution proteomic evidence to map the transition from stable CHIP to overt malignancy. Methods Following PRISMA 2020 guidelines, we analyzed 15 high-quality studies (selected from 83 initial records) published between 2015 and 2025. The review integrates data from diverse proteomic platforms—including DIA-MS, TMT labeling, and Olink high-plex panels across hematopoietic stem/progenitor cells (HSPCs), the bone marrow niche, and blood. Risk of bias was rigorously assessed using ROBINS-E, QUIPS, and SYRCLE frameworks. Results Synthesis of the evidence reveals a profound “Genotype-Proteotype Gap,” characterized by a low median mRNA-protein correlation (0.30) in aging stem cells. Clonal expansion is associated with a non-linear “functional niche failure” exceeding a 5% VAF threshold, marked by the emergence of inflammatory mesenchymal stromal cells (iMSCs) expressing IL-1R1 and CD44. Systemically, proteomic risk scores utilizing markers such as F7, BIN2, and CXCL11 can predict incident myeloid neoplasms over a decade before clinical diagnosis. Evidence strength varies substantially, with high-strength support for plasma predictive signatures and preliminary-to-moderate support for mechanistic findings from smaller cohorts. Conclusion This systematic review identifies that malignant progression is dictated by a qualitative proteomic “switch” and structural niche reorganization. However, causal relationships remain to be definitively established. We identify a critical “Spatial Architecture Gap” in current research, highlighting the need for spatial proteomic platforms to map the physical “handshake” between mutant clones and their inflammatory environment to enable early clinical interception.